UPComp - A PHP Component for Recommendation Based on User Behaviour - Peska, L.; Eckhardt, A.; Vojtas, P. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
In this paper, we investigate the possibilities of interpreting user behaviour in order to learn his/her preferences. UP Comp, a PHP component enabling use of user preferences for recommendation, is described. UP Comp is a standalone component that can be integrated into any PHP web with only basic knowledge of PHP, HTML and SQL. The methods of user behaviour interpretation are evaluated on a real web shop with tourist trips using UP Comp.